Being Agile: The Influence of Agile Project Practices on the Project Team Productivity - AL HAMMADI, ZAINAB AHMED (2018)
Agile project practices and methods have gained more popularity and broadly used due to various benefits. The agile project management sound alternative to the traditional project management and its methods characterised as being flexible and the project is done in iterative approach where deliverables or outcomes are expected at the end of each sprint. It is reported that agile project practices have both negative and positive impact on the project team productivity. The main purpose of this qualitative research is to critically assess the concept of agile project management and to better understand the effect of using agile project practices on the project and how does it affect team’s productivity. In this research both primary and secondary sources are used to collect necessary data concerning the research topic. The secondary date is collected from relevant literatures, selected government departments’ websites and their periodic documents, while the primary data is gathered through in-depth semi-structured interviews with employees at different position and from different department. The theoretical reviews show that agile project management and practices lead to positives results and also some negative outcomes have been identified. The study shows the results of the group interviews conducted at three different government organisations based in the U.A.E. with a total of 13 people from different departments. The findings show that the implementation of agile practices result in positive impacts and outcomes in the three selected projects, although the results vary among the three, as the practices are found to be implemented partially in some projects or ineffectively. In addition, some negative impacts of using practices have been identified. In terms of productivity, most of the used practices showed positive impact on productivity and some affected the productivity indirectly. Whereas, practices such as open office design is found to have both negative and positive impact on productivity, but actions have been taken to minimise its negative impacts. The main limitation to this study is that it only examined three projects and the respondents’ number is thirteen, where the researcher believes that more projects and respondents will add more insight and value to the outcomes. Thus, for future studies, it is recommended to examine more projects and interview more respondents to get more accurate and valid results.